Perluasan Pangsa Pasar dan Peningkatan Pendapatan Mina Collection kudus Melalui Online Marketing - Noor Latifah; Putri Kurnia Handayani; Syafiul Muzid (Muria Jurnal Layanan Masyarakat, 2019)
Online Marketing is a marketing system that uses internet media as a vehicle for product marketing, a company or an effort to offer new products or to gather information from customers about the results of the products produced requires various forms of marketing. One of them can be by utilizing online marketing for media promotion and marketing of products produced effectively and efficiently. Mina Collection Kudus is a UKM engaged in the field of convection that produces products in the form of fashion. During this time in the promotion and marketing of the resulting product is still done manually only by way of going in and out of the market to offer products and depositing goods as requested. So that the promotion and marketing carried out only in certain areas alone can not reach a wider and broader area coverage, the lack of breadth of the scope of the promotion and marketing carried out causes the income obtained is also less than the maximum. The Muria Kudus University dedication team helps in developing the Online Marketing System at the Holy Mina Collection so that it can expand its Market Share and increase revenue effectively and efficiently.